Low-noise magnetoencephalography system cooled by a continuously operating reliquefier. (27th June 2017) - Lee, Y H; Kwon, H; Yu, K K; Kim, J M; Lee, S K; Kim, M-Y; Kim, K
Abstract: We fabricated a low-noise magnetoencephalography (MEG) system based on a continuously operating reliquefier for cooling of low-temperature superconducting quantum interference device gradiometers. In order to reduce the vibration transmission, the gradiometers are mounted in the vacuum space of the helmet dewar with direct thermal contact with the liquid helium helmet. The reliquefier uses a 1.4 W pulse tube cryocooler with a remote motor, and a horizontal transfer tube with a downslope angle of 1°. The white noise of the system is 3.5 fTrms /√Hz (at 100 Hz). The vibration-induced peak at 1.4 Hz is 18 fTrms /√Hz averaged over the whole helmet array of 150 channels, which is the lowest among the reported values using reliquefier cooling and comparable to the noise peak cooled by conventional direct liquid helium cooling with axial gradiometers of the same baseline. The spontaneous brain activity signal showed nearly identical signal quality with the reliquefier turned on and off, and the reliquefier-based MEG system noise is well below the brain noise level.